Superconducting gap and pair breaking in CeRu₂ studied by point contacts - Moskalenko, A.V.; Naidyuk, Yu.G.; Yanson, I.K.; Ōnuki, Y.; Haga, Y.; Yamamoto, E.; Hedo, M.; Inada, Y. (Физика низких температур, 2001)
The superconducting gap in a CeRu₂ single crystal is investigated by point contacts. BCS-like behavior of the gap Δ in the temperature range below Tc* (Tc*<Tc, where Tc is the critical temperature) is established, indicating the presence of a gapless superconductivity region (between Tc* and Tc). The pair-breaking effect of paramagnetic impurities, supposedly Ce ions, is taken into consideration using the Scalski–Betbeder–Matibet–Weiss approach based on Abrikosov–Gorkov theory. It allows us to recalculate the superconducting order parameter Δα (in the presence of paramagnetic impurities) and the gap Δp (in the pure case) for the single crystal and for the previously studied polycrystalline CeRu₂. The value 2Δp(0)≈2 meV, with 2Δp(0)/kBTc≈3.75, is found in both cases, indicating that CeRu₂ is a “moderate” strong-coupling superconductor.